Effect of Microarc Oxidation Treatment with Different Concentrations of MgSiF6 on Titanium-Porcelain Bonding Strength. (8th October 2020) - Lv, Jing; Yuan, Mujie; Sun, Pei; Wei, Changlei; Zhang, Shaojun; Wang, Yaozhong; Liu, Jie; Tan, Fei
Abstract : This study aims to evaluate the effects of different electrolyte concentrations on titanium-porcelain bonding strength after microarc oxidation (MAO) treatment. Four MgSiF6 electrolyte concentrations (10 g/L, 20 g/L, 30 g/L, and 40 g/L) were chosen for the MAO bath solutions. According to ISO 9693, the bonding strengths of titanium-porcelain restorations were detected by the three-point bending test. Scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) were applied to evaluate the morphologies and elemental compositions of the MAO coating, titanium-porcelain fracture surfaces, titanium-porcelain interfaces, and oxygen diffusion. The bonding strength of the 20 g/L MgSiF6 group was significantly higher than that of the control group. However, overly high MgSiF6 concentrations had a negative influence on the bonding strength between titanium and porcelain. The results demonstrate that MAO treatment with only appropriate electrolyte concentration can improve the titanium-porcelain bonding strength.